2020
DOI: 10.1038/s41419-020-2349-8
|View full text |Cite|
|
Sign up to set email alerts
|

Clarithromycin inhibits autophagy in colorectal cancer by regulating the hERG1 potassium channel interaction with PI3K

Abstract: We have studied how the macrolide antibiotic Clarithromycin (Cla) regulates autophagy, which sustains cell survival and resistance to chemotherapy in cancer. We found Cla to inhibit the growth of human colorectal cancer (CRC) cells, by modulating the autophagic flux and triggering apoptosis. The accumulation of cytosolic autophagosomes accompanied by the modulation of autophagic markers LC3-II and p62/SQSTM1, points to autophagy exhaustion. Because Cla is known to bind human Ether-à-go-go Related Gene 1 (hERG1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 71 publications
1
45
0
Order By: Relevance
“…In the study of inhibiting radiation-induced autophagy to sensitize malignant glioma cells, it found that autophagy could enhance cell apoptosis, while inhibiting autophagy did not affect the function of cell apoptosis, indicating that autophagy may not directly lead to cell death, but only played a promoting role [ 41 ]. This relationship between autophagy and apoptosis has also been found in studies of colorectal cancer [ [42] , [43] , [44] ]. Petroni G et al found that Cla induced and blocked autophagy by regulating both the PI3K/Akt pathway and the herg1-dependent regulation of P53 in colorectal cancer.…”
Section: The Main Way Of Crosstalk Between Autophagy and Apoptosis Insupporting
confidence: 69%
See 1 more Smart Citation
“…In the study of inhibiting radiation-induced autophagy to sensitize malignant glioma cells, it found that autophagy could enhance cell apoptosis, while inhibiting autophagy did not affect the function of cell apoptosis, indicating that autophagy may not directly lead to cell death, but only played a promoting role [ 41 ]. This relationship between autophagy and apoptosis has also been found in studies of colorectal cancer [ [42] , [43] , [44] ]. Petroni G et al found that Cla induced and blocked autophagy by regulating both the PI3K/Akt pathway and the herg1-dependent regulation of P53 in colorectal cancer.…”
Section: The Main Way Of Crosstalk Between Autophagy and Apoptosis Insupporting
confidence: 69%
“…The former is related to the reduction of the phosphorylation levels of Akt and erk1/2, while the latter is related to the inhibition of autophagy flux. Late damage of autophagy-mediated degradation triggers apoptotic cell death, which is caused by activation of P53 and caspases [ 42 ]. The stereoselective assembly of Multifunctional Spirocyclohexene pyrazolone also induced autophagy-dependent apoptosis in colorectal cancer cells [ 43 ].…”
Section: The Main Way Of Crosstalk Between Autophagy and Apoptosis Inmentioning
confidence: 99%
“…Moreover, obatoclax which exhibits pan-Bcl-2 inhibition effect has been demonstrated to cause a striking inhibition of autophagy at late-stage in colorectal cancer and bladder cancer cells (Huang and Sinicrope, 2010;Koehler et al, 2015;Jiménez-Guerrero et al, 2018). Clarithromycin is a macrolide antibiotic frequently utilized in the treatment of upper and lower respiratory tract infections and Helicobacter pylori that has demonstrated inhibitory effects on autophagy (Altman and Platanias, 2012;Giulia Petroni et al, 2020). Resveratrol is a natural polyphenolic compound derived from plants which has proapoptotic effects on various cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Clarithromycin, a macrolide antibiotic, is used to treat upper and lower respiratory tract and Helicobacter pylori infections ( Crowe, 2019 ). Clarithromycin suppresses autophagy by inhibiting the interaction between the hERG1 potassium channel and PI3K in colorectal cancer ( Altman and Platanias, 2012 ; Petroni et al ., 2020 ). Elaiophylin, a macrolide antibiotic with immunosuppressive properties, inhibits the autophagic flux and has anti-tumor activity in ovarian cancer ( Zhao et al ., 2015 ) and multiple myeloma with mutant TP53 ( Wang et al ., 2017 ).…”
Section: Autophagy Inhibitors In Cancer Therapymentioning
confidence: 99%